THE IMPACT OF INTER-MUNICIPAL COOPERATION OF TERRITORIAL COMMUNITIES ON LOCAL SUSTAINABLE DEVELOPMENT - DUVANOVA, OKSANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article confirms that inter-municipal cooperation is a factor influencing the determinants of sustainable local development. The relationship between the number of communities that have concluded agreements on inter-municipal cooperation and a set of indicators of the indicators of sustainable development of territorial communities is formalized based on the use of the correlation-regression analysis toolkit using the STATA software package. There is a positive impact of increasing the number of communities that have concluded agreements on inter-municipal cooperation on the indicators of the economic component of sustainable development: gross regional product, agricultural output, exports of goods per capita; on the environmental component of sustainable development: reducing the growth rate of pollutant emissions from stationary sources of pollution and reducing the amount of fuel and energy resources consumed in the region. Regarding the indicators of the social component of sustainable development, there is a positive impact on the regional human development index, the share of graduates of secondary schools who received 160 points and above according to the results of external independent evaluation of Ukrainian language and literature, the planned capacity of outpatient clinics, average life expectancy at birth and reduction of а number of criminal offenses committed against human life and health. Dissemination of inter-municipal cooperation is a promising area for the development of territorial economic systems. It is not only an alternative to the consolidation of communities but also an effective means of ensuring the economic viability of communities in the context of decentralization. Today, inter-municipal cooperation of territorial communities in Ukraine is one of the important directions of local self-government reform.